2016
DOI: 10.1016/j.bbi.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell morphological and density changes through the lifespan of rhesus macaques

Abstract: How aging impacts the central nervous system (CNS) is an area of intense interest. Glial morphology is known to affect neuronal and immune function as well as metabolic and homeostatic balance. Activation of glia, both astrocytes and microglia, occurs at several stages during development and aging. The present study analyzed changes in glial morphology and density through the entire lifespan of Rhesus macaques, which are physiologically and anatomically similar to humans. We observed apparent increases in gray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
92
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 58 publications
10
92
0
1
Order By: Relevance
“…To address his question, we stained 6μm paraffin sections with GFAP antibodies as is routine in this lab (Inglis et al, 2015; Lee et al, 2013a; Lee et al, 2013b; Robillard et al, 2016; Snook et al, 2013). To determine if DENV infection affected the density of astrocytes in macaque frontal lobe, the number of GFAP positive cells per unit area was calculated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address his question, we stained 6μm paraffin sections with GFAP antibodies as is routine in this lab (Inglis et al, 2015; Lee et al, 2013a; Lee et al, 2013b; Robillard et al, 2016; Snook et al, 2013). To determine if DENV infection affected the density of astrocytes in macaque frontal lobe, the number of GFAP positive cells per unit area was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…To determine how astrocyte activation translated into altered overall morphology, fluorescent images of GFAP immunopositive cells were imported into Neurolucida as is routine (Inglis et al, 2015; Lee et al, 2013a; Lee et al, 2013b; Renner et al, 2013; Robillard et al, 2016; Snook et al, 2013). The morphometrics of the cells were then calculated to determine if DENV infection induced an atrophy or hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about CCL2 protein in this context, but this chemokine has been found to co-localize with neurons, astrocytes, and microglia in healthy adult, alcohol naive, Wistar, and alcohol-preferring rats (Banisadr et al 2005a; June et al 2015). Both astrocytes and microglia undergo phenotypic changes with age including morphological changes and changes in expression of neuroimmune molecules (Bushong et al 2004; Crain et al 2013; Robillard et al 2016; Schwarz et al 2012; Yang et al 2013). Therefore, it would be important to determine the potential changes across age in cell-type distribution of CCL2 protein in response to alcohol and other challenges such as stress.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study identified changes that occurred across the lifespan in healthy macaques [3]. Our data showed increased branching, and hence connectivity of astrocytes aged from juveniles through adolescence and into adulthood.…”
Section: Introductionmentioning
confidence: 54%
“…We have utilized the rhesus monkey ( Macaca mulatta ), a “gold standard” system that has been in use since the 1960’s and has proven to have very high translational validity with respect to having a distinct adolescent period and cognitive assessments [1], combined with a true geriatric period [2]. A unique opportunity existed, therefore, to quantify glial morphometrics in primates with eugeric aging [3]. Crucially, rhesus macaques age approximately 4 times the rate of humans [46], providing a useful cohort of animals at Tulane National Primate Research Center.…”
Section: Introductionmentioning
confidence: 99%